2022
DOI: 10.1002/cre2.540
|View full text |Cite
|
Sign up to set email alerts
|

Is the degree of facial swelling after dental extraction sufficient to justify the current delays to radiotherapy mask production? A pilot evaluation of postextraction swelling using 3D photography

Abstract: Background Concern that facial swelling after dental extractions will spoil the fit of radiotherapy masks in head and neck cancer patients leads to the current practice of delay making of mask production (and therefore the start of radiotherapy) for several days or longer. However, there is little data on how extensive facial swelling is after dental extraction. Aim To assess the degree of facial swelling in a group of adult patients attending Newcastle Dental School fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Comprehensive future studies are necessary to establish equivalency and investigate factors influencing operation time and complication rates. Additionally, the exploration of advanced 3D measurement techniques for assessing postoperative edema and swelling could provide a more nuanced understanding of surgical outcomes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive future studies are necessary to establish equivalency and investigate factors influencing operation time and complication rates. Additionally, the exploration of advanced 3D measurement techniques for assessing postoperative edema and swelling could provide a more nuanced understanding of surgical outcomes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were asked to distinguish between the number of contacts on the oral mucosa and skin while their eyes were closed. If two points could be distinguished at less than 7 mm, it was considered normal; at a distance between 7 and 11 mm, it was considered slightly aberrant; and if it could only be distinguished at a distance greater than 11 mm, sensitivity was considered impaired [ 32 ]. The graft was considered successful when there was no infection or graft loss.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the considerable quantity of image acquisition systems presently employed for 3D photography, research use for this type of imaging is limited to a handful of devices, of which 2 are the most extensively utilized. First, we found that the most used system was the 3dMD, 10,[12][13][14][15][16][17][18][19][20][21][22][23][24] which consists of 2 groups of 3 cameras, each located at 45 degrees to the right and left side target, and was used by 52% of the authors, followed by the Vectra M3, [25][26][27][28][29][30][31][32] which consists of a device composed of 3 groups of 2 cameras each and was used by 28% of the authors. In contrast, some other systems were used by some authors.…”
Section: System Usedmentioning
confidence: 99%
“…In contrast, most of the authors used chairs with high backs to improve back support, reducing variations due to mobility or changes in body posture. [12][13][14][15][16]18,19,25,[27][28][29][30][31][32][33]36,37,41 Head Posture Riml et al (2011) 42 showed the influence of head position on facial analysis, noting that different postures yield different results in measurements on facial photographs. In this study, most authors describe the positioning of the head for image acquisition as: "natural head position," (NHP) noting that this is a reproducible and proven position, described as "the head positioned in a relaxed manner while the person observes a fixed point on the horizon."…”
Section: Body Posturementioning
confidence: 99%
See 1 more Smart Citation